HUBUNGAN POLA ASUH ORANG TUA DENGAN PERNIKAHAN USIA DINI DI WILAYAH KERJA PUSKESMAS BENGKALIS - Nurhaliza, Nurhaliza; Yanti, Rifa; Mardiya, Rizka; Tanberika, Fajar Sari (Ensiklopedia of Journal, 2025)
Early marriage is one of the problems faced in many countries. The causes are various, such as economic problems, customs and education, and values instilled by parents. Early marriage has consequences such as reproductive health risks and increased fertility and so on. The application of appropriate parenting patterns in guiding and educating children is very necessary because one of the biggest problems due to early marriage is how to educate and raise children with good parenting patterns and in accordance with the needs of children because adolescence is the beginning of the process of maturity. The purpose of this study was to determine the Relationship between Parenting Patterns and Early Marriage in the Bengkalis Health Center Work Area, Bengkalis Regency. Type of research Quantitative research with analytical observational design, The population in this study were all women who married early under the age of 19 in the Bengkalis Health Center Work Area as many as 40 people with a sample size of 20 people. The sampling technique used Purposive Sampling. The instrument used was a Questionnaire. The results of the study were analyzed using univariate analysis and the Chi Square test. The majority of respondents who married at an early age indicated that their parenting style was permissive (50.0%). The majority of respondents married at an early age (65.0%) and there is a relationship between parenting patterns and early marriage in the Bengkalis Health Center Work Area, Bengkalis Regency. with p value = 0.033. This study shows that there is a relationship between parenting patterns and early marriage in the Bengkalis Health Center Work Area, Bengkalis Regency. It is hoped that parents will be wise in guiding and directing their children, so that children can choose the right decisions, especially in matters of marriage. Keywords: Parenting, Early Marriage, Parents